Environmental Justice: A Case of Socio-environmental Vulnerability in Rio de Janeiro - da Costa Silva, Gabriela (Environnement Urbain / Urban Environment)

(untitled) (Réseau Villes Régions Monde, 2010)
Environmental justice addresses the unequal environmental burden often borne by minorities and low-income populations. In Brazil, many studies confirm extreme socio-environmental inequities in urban areas. Analysis based on socio-environmental vulnerability allows us to understand the intra-urban spatial distribution of socio-environmental differences and to provide insight for the development of planning policies that enhance the capacity of communities to respond to multiple risks (social, environmental, etc.) (Mendonça, 2004). This study examines the levels of socio-environmental vulnerability in the Jacarepaguá lowlands of Rio de Janeiro, taking into account the existing strengths and limitations of public administrations in their efforts to balance private and public interests in regards to environmental justice.